Benefits and Challenges in Mastering Speaking Skills through Animated Movies: Students’ Perspective - Wijayanto, Dimas; Mulyadi, Dodi; Wijayatinningsih, Testiana Deni (Universitas Dian Nuswantoro, 2025)
This research investigates the perspectives of eighth-grade students at SMPN 2 Semarang on the benefits and challenges of mastering English-speaking skills through animated movies. A mixed-method approach was employed in this study, integrating both qualitative and quantitative techniques. Data were collected through closed- and open-ended questionnaires and semi-structured interviews. The questionnaire was distributed to 108 eighth-grade students, while nine students were selected for in-depth interviews. The quantitative data from the questionnaires were analyzed using SPSS to identify statistical trends. At the same time, the qualitative responses from interviews were examined using NVivo software to code and categorize students’ perspectives. This combination provided comprehensive insights into the benefits and challenges of using animated movies in mastering English-speaking skills. The findings revealed that animated movies provided substantial benefits, particularly in enhancing vocabulary acquisition, increasing motivation, improving pronunciation, and boosting students’ self-confidence. Most students expressed that the visual and auditory nature of animated movies made it easier for them to understand and remember new vocabulary, learn correct pronunciation, and practice speaking more enjoyably. Nevertheless, some challenges remained, particularly in mastering grammar and overcoming anxiety when speaking in front of others. Despite these challenges, the study concludes that animated movies are effective and engaging tools for developing speaking skills and recommends their use in the English language learning process. The study's results provide insights for teachers, learners, and educational institutions in selecting appropriate media to support English instruction.